2022
DOI: 10.1002/aepp.13232
|View full text |Cite
|
Sign up to set email alerts
|

Meet the meatless: Demand for new generation plant‐based meat alternatives

Abstract: With the unique mimicry of the sensory experiences of meats, the plant‐based meat alternatives (PBMA) appeal to consumers outside the traditional vegetarian demographics. This study analyzes market expenditure data from 2017 to 2020 to evaluate the demand for PBMA in relation to meats. Results show that PBMA is a complement for beef and pork while a substitute for chicken, turkey, and fish. Although the current market demand for PBMA is still incomparable with meats, the growth of PBMA sales is significant. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…This can be interpreted as consumers demonstrating higher purchasing power when they expect to benefit from purchasing PBMA. Zhao et al [ 66 ] analyzed modern consumers’ demands for PBMA and found that consumers are benefitted in terms of the environment, health, and economy. Since PBMA is produced from plant-based materials, it can be purchased at a more reasonable price, reduce environmental pollution, and improve consumers’ diet and health [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be interpreted as consumers demonstrating higher purchasing power when they expect to benefit from purchasing PBMA. Zhao et al [ 66 ] analyzed modern consumers’ demands for PBMA and found that consumers are benefitted in terms of the environment, health, and economy. Since PBMA is produced from plant-based materials, it can be purchased at a more reasonable price, reduce environmental pollution, and improve consumers’ diet and health [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [ 66 ] analyzed modern consumers’ demands for PBMA and found that consumers are benefitted in terms of the environment, health, and economy. Since PBMA is produced from plant-based materials, it can be purchased at a more reasonable price, reduce environmental pollution, and improve consumers’ diet and health [ 66 ]. PBMA food marketing teams must extol the advantages of PBMA in various ways and promote it actively by providing information about its positive effects in engaging ways, such as by involving popular figures.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that plant-based alternatives cannot compete with meat in terms of flavor, texture and taste. (Zhao et al, 2022) Consumers often buy both animal-based products and plant-based ones at the same time, to compare. Then, they usually revert back to the animal-based product, unsatisfied with the plant alternative.…”
Section: Potential Solutionsmentioning
confidence: 99%
“…Moving toward consuming plant-based meat while shifting away from conventional meat may benefit the environment, animal welfare, and human health ( 1 ). For many decades, conventional plant-based proteins such as seitan, tempeh, and tofu, as well as other vegetarian meat-like foods, have been commercially accessible ( 2 ). However, plant-based food demands have significantly increased over the last decades, especially in Western countries ( 3 ).…”
Section: Introductionmentioning
confidence: 99%